A multi-binding site hydrazone-based chemosensor for Zn(ii) and Cd(ii): a new strategy for the detection of metal ions in aqueous media based on aggregation-induced emission. Issue 4 (14th January 2021) - Wu, Min; Yang, Dong-Dong; Zheng, Han-Wen; Liang, Qiong-Fang; Li, Jia-Bin; Kang, Yang; Li, Sai; Jiao, Chen; Zheng, Xiang-Jun; Jin, Lin-Pei
Abstract : A new detection strategy based on AIE was developed to detect Cd(ii ) and Zn(ii ) ions in aqueous media via the off–on mode. Abstract : A multi-binding site chemosensor, N -(3-methoxy-2-hydroxybenzylidene)-3-hydroxy-2-naphthahydrazone (H3 L), with excited-state intramolecular proton transfer (ESIPT) behaviour was prepared and characterized. It possesses no aggregation-induced emission (AIE) characteristics but can detect Cd 2+ and Zn 2+ ions selectively in the "off–on" mode based on the AIE of their complexes in the media of THF/HEPES and THF/H2 O, respectively, which will provide a new strategy for target detection based on AIE. The detection limits of Zn 2+ and Cd 2+ were 9.85 × 10 −9 M and 1.27 × 10 −7 M, respectively. The aggregates of the complexes formed in the detection system were confirmed by DLS data and SEM images. The corresponding Zn 2+ (1 ) and Cd 2+ (2 ) complexes were prepared to investigate the response mechanism. Powder X-ray diffraction and single crystal X-ray diffraction proved that complex 1 is the species formed in the detection system. The chemosensor coordinates with the Cd 2+ and Zn 2+ ions in different formation and coordination modes, leading to the emission position of the aggregates at 560 and 645 nm, respectively, based on which Cd 2+ ions were successfully differentiated from Zn 2+ ions. Moreover, the detection of Cd 2+ and Zn 2+ ions was realized qualitatively via test paper and quantitatively in water.